Improving Students' Awareness of the Quality of Brantas River and Its Environment - Herawati Susilo (Jurnal Ilmu Pendidikan, 2016)
Beginning 1996, trainings for Biology, Chemistry, Geography and Economics teachers (and again in 1998) were conducted to help them integrate river as learning resources into their subject matter. Students from 29 SMUs along the Brantas River are brought to the river to learn to check the quality of water chemically and biologically, and to measure some physical conditions of the water. The economical use of the river were also observed and discussed. It is expected that the students will be aware of the quality of water and of the value of water resources. Competitions have been conducted to increase students' enthusiasms in studying the river and its environment. As a result of these activities, a network of schools around the river has been initiated which was called the Communication Network of Schools doing the checking of the Water Quality